Estimating Monthly New Car Sales in Turkey with Artificial Neural Networks (ANN) and ARIMA Models - Eşidir, Kamil Abdullah; Gür, Yunus Emre; Yoğunlu, Vahap; Çubuk, Muhammed (Pamukkale Üniversitesi, 2022)
In the study, monthly new car sales in Turkey were estimated with Arima, which is one of the Time Series Analysis models, and Artificial Neural Networks (ANN), which is one of the artificial intelligence-based prediction models. The dependent variable is monthly new car sales. The independent variables are monthly car exports (USD), monthly car imports (USD), monthly US Dollar exchange rates (TL), monthly Turkey exports (USD) and monthly Turkey imports (USD). Using monthly data (January 2002-December 2020, 228 months-19 years) obtained from the Turkish Statistical Institute (TUIK), the Central Bank of the Republic of Turkey (TCMB), the number of new car sales for 15 months, between January 2021 and March 2022 has been estimated. The performance of the ANN model was compared with the Arima model, the differences of the estimations and the results were interpreted. In the study, it was determined that the Arima model have better results than the ANN model.

Çalışmada, yapay zekâ temelli tahmin modellerinden Yapay Sinir Ağları (YSA) ve Zaman Serileri Analizi modellerinden Arima ile Türkiye’deki aylık sıfır km otomobil satış adetleri tahmin edilmiştir. Bağımlı değişken aylık sıfır km otomobil satışlarıdır. Bağımsız değişkenler ise aylık otomobil ihracatı (USD), aylık otomobil ithalatı (USD), aylık Amerikan Dolar kuru (TL), aylık Türkiye ihracatı (USD) ve aylık Türkiye ithalatı (USD)’dir. Türkiye İstatistik Kurumu (TÜİK), Türkiye Cumhuriyet Merkez Bankasından (TCMB) elde edilen aylık veriler (Ocak 2002-Aralık 2020, 228 ay-19 yıl) kullanılarak, Ocak 2021 ile Mart 2022 arasında gerçekleşen 15 aylık sıfır km otomobil satış adetleri tahmin edilmiştir. YSA modelinin performansı Arima modeli ile karşılaştırılmış, tahminlerin farkları ve sonuçlar yorumlanmıştır. Çalışmada Arima’nın YSA’ya kıyasla daha iyi sonuç verdiği tespit edilmiştir.
Yapay Sinir Ağları (YSA) ve ARIMA Modelleri ile Türkiye’de Aylık Sıfır km Otomobil Satış Adetlerinin Tahmin Edilmesi
Keywords: Operation; Yöneylem